(untitled) (Proceedings of Southern Federal University. Philology, 2024)
DOI 10.18522/1995-0640-2024-3-84-92 This article is devoted to the peculiarities of the names of persons by their professional activity expressed by English borrowings or having in their composition a supporting component of the English origin, in the Russian-speaking Internet space. The work considers the structural and wordformation features and thematic classification of the names of a person by the professional activity in the Russian-speaking Internet space; presents the results of the analysis of the peculiarities of assimilation, linguistic adaptation and the word-formation process of English borrowings, denoting the names of persons by their professional activities in the Russian-speaking Internet space. The scientific novelty of the work is presented in the complex development of the peculiarities of the names of persons by their professional activities in the Russian-speaking Internet space. As a result of the study, 188 names of persons by the professional activity have been identified, which are expressed by English-language borrowings or have a supporting component of the English origin in their composition, 3 thematic classifications of names of persons by the professional activity in the Russian-language Internet space have been identified. To analyze the material under study the following methods have been used in the work: contextual method, in order to establish the features of actualization of the units in the type of text under study; a method of linguopragmatic analysis, which allows us to identify the dependence of the use of various means of expression in the Russian language fund on elements of material and behavioral culture and a descriptive method for identifying the characteristic features of English borrowings in mass media discourse. The relevance of this study is due to the active process of penetration and functioning of English-language vocabulary in the modern Russian language, as well as the high importance of digital and Internet technologies, social networks, the transition of many areas of business from offline to online mode and the need to create new names for person’s professional activity. This work allowed us to come to the conclusion about the productivity of the Russian word-formation models confirming the ability of the Russian language to adapt foreign words and adding new connotations to them. It is proved that by accepting and adapting foreign vocabulary in its lexico-grammatical system, the modern Russian language adapts to such rapid changes in the world very quickly and flexibly. The results of the study can be used in the preparation of reference and study materials. Key words: English-language borrowings, professional activity, multilevel entry, structural and word-formation features, thematic classification, Internet space